Geochemical analysis and quality assessment of geothermal water in Gujarat, India - Pandey, Vaishnavi; Chotaliya, Bhavy; Bist, Namrata; Yadav, Kriti; Sircar, Anirbid (Energy Geoscience, 2023)
Geothermal water can have a wide range of direct applications, including drinking, domestic use, irrigation and industrial use. This study analyses geothermal water from Dholera, Diu, Gandhar, Kutch, Porbandar, Tulsishyam, and Unai regions located in Gujarat, India, to determine the hydrochemistry for establishing the water's suitability for drinking and irrigation purposes. From each region, three different water samples were collected. For drinking purpose, total eleven water quality parameters such as pH, electrical conductivity, total dissolved solids, calcium, magnesium, sodium, potassium, chloride, sulphate, carbonate and bicarbonate were evaluated. Piper and Durov plots were used to understand the ionic composition and evolution of water. Whereas for irrigation, the parameters such as total dissolved solids, sodium absorption ration, electrical conductivity, and potential salinity were used for water quality check. Wilcox Plot was plotted to understand the sodium and salinity hazard of water. Water quality index and irrigation water quality index were used to assess the water quality for making the analytical procedure easy. The findings indicate that the water samples from the Dholera and Diu areas had extremely high values for both the water quality index and total dissolved solids content. Water in these places may be appropriate for making salt. All the other samples show adequacy for utilization in irrigation purpose. [Display omitted] •Geochemical analysis of seven geothermal potential zones.•Water quality index analysis to evaluate the suitability of groundwater for drinking.•Water quality index analysis for irrigation.